Correlation Between History of Infectious Disease with Stunting in Toddler - Mahudeh; Nikmatur Rohmah; Sri Wahyuni Adriani (Journal of Nursing Science Update (JNSU), 2022)
Stunting is a chronic nutritional problem caused by a long period of malnutrition. Prolonged malnutrition can decrease body resistance, making it susceptible to disease. This study aims to analyze the correlation of the history of infectious disease with stunting cases in toddlers at the Working Area of Sumberjambe Health Center. The research design used a correlation design with a cross-sectional study approach. The sample of this research was 376 toddlers. For the sampling technique, we used stratified random sampling. The research was conducted in May 2021 using questionnaire instruments. Analyze the data using the Spearman Rho test with an α = 0.05. Result: Based on data analysis obtained from 376 respondents, 274 respondents (72.9%) experienced a history of diseases with frequent categories, and 102 respondents (27.1%) experienced a history of diseases with infrequency categories. This study concludes with a correlation between historical infectious diseases and stunting. Based on the results regarding health promotion, the prevention of recurrent or sustainable pain in toddlers needs to be improved to overcome the problem of stunting. Moreover, giving health promotion advice for mothers to provide exclusive breast milk and nutritious food and maintain food hygiene and shelter for children are essential to avoid stunting.